Educação inclusiva e a psicologia humanista centrada na pessoa: implicações das teses educacionais rogerianas - Santos Filho, José Antônio dos (2024)
Inclusion in education constitutes a movement of openness, acceptance and appreciation of the student's difference, in the educational context in which they are inserted. In Brazil, the idea is defended that educational institutions must commit to ensuring access, participation and permanence of students in regular schools and, precisely for this reason, currently, there is a political and social movement, with ethical implications, breaking paradigms and breaking rigid structures in the exclusion scenario. The Person-Centered Approach was developed by the American psychologist Carl Ransom Rogers, based on his clinical experiences with “maladjusted” children. Subsequently, the author developed an educational proposal that goes against the grain of North American educational institutions, inspired by his clinical method, centered on the client, and based on the significant experiences brought by students, which he called Student-Centered Teaching. Although he was concerned with issues concerning education and its phenomena, Rogers did not mention inclusion in his clinical and educational works. In this way, it is up to post-Rogerian researchers to develop research that is committed to this phenomenon in Brazil, since one of the ramifications of this theory is concerned with human relationships and their disputes. Thus, the present dissertation work aimed to theoretically and critically analyze the phenomenon of inclusive education in light of Carl Rogers' Humanistic Psychology. This nickname is understood as a term that brings together all the work developed by Rogers and his scholars and followers. Based on this main objective, the following were listed as specific objectives: synthesizing the educational theses elucidated by Rogers throughout his works; systematize bibliographic documents that organize inclusive policies in the Brazilian context; interpret Rogerian educational theses synthesized based on analyzed documents. Therefore, this dissertation was divided into three chapters: chapter 1 starts from a theoretical and conceptual understanding of the phenomenon of education in Rogerian works, taking as inspiration the historical-critical perspective of epistemological research in psychology, linked to the contributions of reading techniques in bibliographical research and conceptual research in psychology; chapter 2 systematizes documents that organize inclusive policies in the national context, inspired by documentary research and reading techniques from bibliographic research; chapter 3 brings, based on theoretical conceptions about Rogers' educational theses and documents that discuss inclusion in education, elaborations of Person-Centered Humanistic Psychology for the field of inclusive education, using, again, techniques of reading. It is concluded that it is possible to develop inclusive practices in Rogers' Humanistic Psychology, as social and political dimensions are considered. From this, enable greater implementation of what is already assured in documents and regulations on the rights of people with disabilities and, also, adapt Rogerian methods within training policies and institutions.